THE LEADERSHIP OF KYAI IN ISLAMIC BOARDING SCHOOL (Study on Islamic Boarding School in the City of Jambi) - Anwar, Kasful (2010)
This study was conducted based on the problem of kyai leadership pattern in Islamic boarding school in the city of Jambi which seems still paternalistic and centralized. In other words, the leadership pattern is still centered on the kyai as the holder of the highest authority. Meanwhile, the development of Islamic boarding schools in Jambi has been decreasing in the last decade because the differences of kyais abilities at recent time with their predecessor, so that only a small number of Islamic boarding schools still exist in the society at present time The study aims is to explore how effective the leadership of kyai in Islamic boarding school in the city of Jambi in which be explored with several research questions which are; 1) What system that is used in the election of Islamic boarding school leader? 2) What kind of leadership model which is used in Islamic boarding school Jambi? 3) How effective the leadership of kyai according to the determination of Islamic boarding school vision, mission, management and policy maker? 4) what is the role of kyai as the leader of Islamic boarding school among the society Qualitative design was used in this study and purposive sampling was employed to determine the respondents. Observation, interview and documentation were used as data collection tools. Interactive model of data analysis was employed to analyze the data in this study which consist of three activities which are data reduction, data display and conclusion. The reliability of result were obtained with the extension of participation technique, intense observation technique and data triangulation. The result of study showed; 1) PP Nurul Iman uses deliberation and consensus system leader in which teachers, board of trustees and coordinator of Pecinan are participating in when electing the leader and the model of leadership in this school is charismatic. PP As'ad leader election is based on family tree system and the model of leader ship in this school is paternalistic. In PKP Al-Hidayah the leader is elected directly by the government of Jambi province as the owner of the school. 2) in general the model of leadership which is used in Islamic boarding school at Jambi use collective-passive model because generally Islamic boarding school at Jambi are under the management of particular foundation.3) The leadership of kyai is not effective because the management system which is applied not optimal. 4) The role of kyai among the society exists in harmony. Based on the research findings, democratic and open election system are recommended in Islamic boarding school leader election to respect individual right to consider leader credibility, quality and acceptability. Islamic boarding schools have to continue to resolve their weaknesses without losing their original character as educational, religion and social institutions as well as applying professional management with collective leadership model in Islamic boarding school system.